2016
DOI: 10.22456/1679-9216.81294
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Heidelberg Isolated from Poultry Shows a Novel Resistance Profile

Abstract: Background:The development of antimicrobial resistance in bacteria is a serious public health issue worldwide. Salmonella spp. is considered a leader cause of gastrointestinal disease in animals and humans, and poultry products have been reported as an important reservoir of the bacterium. S. Heidelberg became lately one of the most prevalent serovars found in several countries. However, hardly any information is available about the epidemiology and the resistance profile of it. Therefore, the objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…As already reported by Neves et al [14] and Krumperman [7], the present study shows that SH is a real challenge regarding antimicrobial resistance when tested against antibiotics routinely used in the treatment of samonelosis in veterinary and human medicine. These authors obtained similar results for the different classes of antimicrobials tested, a fact that may also be related to horizontal transmission of resistance genes.…”
Section: Discussionsupporting
confidence: 77%
“…As already reported by Neves et al [14] and Krumperman [7], the present study shows that SH is a real challenge regarding antimicrobial resistance when tested against antibiotics routinely used in the treatment of samonelosis in veterinary and human medicine. These authors obtained similar results for the different classes of antimicrobials tested, a fact that may also be related to horizontal transmission of resistance genes.…”
Section: Discussionsupporting
confidence: 77%
“…The previous studies have reported that Salmonella spp. strains isolated from animal products were MDR strains in Colombia [ 22 ] and Brazil [ 23 ]. In the present study, we detected a high percentage of Salmonella strains that were phenotypically resistant to STR (79.5%); these findings are consistent with the previous studies that reported that strains isolated from broiler farms in Cundinamarca (Colombia) [ 22 ] and in the United States [ 24 ] exhibited a high percentage of resistance to STR.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have reported that Salmonella spp. strains isolated from animal products were MDR strains in Colombia [22] and Brazil [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another important fact related to Salmonella spp. is the constant description of resistance to various antimicrobials, such as those of the quinolone class (Duarte et al 2009, Mion et al 2014, Casas et al 2016, Neves et al 2016, Rodrigues et al 2017. Resistance in Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%